TINDAK TUTUR PERLAWANAN MARAH RUSLI - Arju Susanto; Hadijah Hadijah (Universitas Nasional, 2019)
This research has analyzed Memang Jodoh by Marah Rusli using descriptif kualitative method and John Langshaw Austin’s Speech-acts theory in perspective Illocutionary acts. I have taken opposite category at this illocutionary. After analyzing and discussing this research, I’ve discovered that Hamli’s opposite illocutionary act was manifested the illocutionary of the author, Marah Rusli. There are a few kind of opposite in Memang Jodoh; opposite about compulsory to work as a men, opposite to hold Minangkabau’s regress tradition, opposite to marriage tradition in Minangkabau’s culture, and opposite to conservatives thought in people of Padang about education. Hence, with this research we know that Rusli’s opposite illocutionary act was denied a few of Minangkabau tradition causing the regress of human being. Besides, the traditions are according to opposite illocutionay aren’t relevance on this age.